Suscetibilidade in vitro de isolados de Sporothrix schenckii frente à terbinafina e itraconazol In vitro susceptibility of isolates of Sporothrix schenckii to terbinafine and itraconazole - Ana Raquel Mano Meinerz; Patrícia da Silva Nascente; Luiz Filipe Damé Schuch; Marlete Brum Cleff; Rosema Santin; Cristiane da Silva Brum; Márcia de Oliveira Nobre; Mario Carlos Araújo Meireles; João Roberto de Braga Mello (Revista da Sociedade Brasileira de Medicina Tropical, 2007)
O estudo objetiva determinar a atividade in vitro da terbinafina e itraconazol através da técnica de microdiluição em caldo (NCCLSM27-A2) adaptado para um fungo dimórfico frente a 12 isolados de Sporothrix schenckii, sendo seis de esporotricose felina, três de esporotricose humana, um isolado de cão e dois isolados humanos provenientes do Instituto Oswaldo Cruz (IOC). O inóculo e as concentrações antifúngicas foram distribuídas em microplacas, as quais foram incubadas a 35°C por cinco dias, quando foi realizada a leitura da concentração inibitória mínima. A concentração inibitória mínima para a terbinafina variou de 0,055µg/ml a 0,109µg/ml e para o itraconazol de 0,219µg/ml a 1,75µg/ml, sendo que para ambos os fármacos as CIMs entre os isolados do IOC foi de 0,875µg/ml. O estudo demonstrou uma alta suscetibilidade do Sporothrix schenckii frente à terbinafina, necessitando mais estudos que correlacionem os testes in vitro frente ao fármaco com a resposta clínica em pacientes com esporotricose. The study objective was to determine the in vitro activity of terbinafine and itraconazole through the microdilution technique in broth (NCCLSM27-A2), adapted for dimorphic fungus, in relation to 12 isolates of Sporothrix schenckii. Six were from feline sporotrichosis, three from human sporotrichosis, one from a dog and two from human isolates originating from Instituto Oswaldo Cruz. The inoculum and antifungal concentrates were distributed on microplates that were incubated at 35°C for five days. Minimum inhibitory concentration readings were made at the end of this period. The MIC for terbinafine ranged from 0.055µg/ml to 0.109µg/ml, and the MIC for itraconazole ranged from 0.219µg/ml to 1.75µg/ml. For both drugs, the MIC from the isolates from IOC was 0.875µg/ml. The present study demonstrates the high susceptibility of Sporothrix schenckii to terbinafine. Further studies to correlate the in vitro susceptibility tests with the clinical response of patients with sporotrichosis are needed.